Infant Lumbar Puncture: POISE Pediatric Procedure Video - Marc Auerbach; Todd Chang; Amanda Krantz; Kevin Ching; Martin Pusic; David Kessler; Anh Nguyen; Deepak Penesetti (Association of American Medical Colleges, 2011)
Abstract Introduction This instructional video reviews the specific discrete steps of the infant lumbar puncture (ILP) procedure, the indications and contraindications of the procedure, the necessary equipment, and troubleshooting methods related to the procedure. ILP is a procedure by which cerebrospinal fluid is collected from the vertebral canal in patients suspected to have central nervous system infections. It is frequently performed by physicians-in-training on infants presenting with fever or irritability. These new interns are called upon to perform infant lumbar punctures with minimal training and self-report very low confidence and limited prior experience or training with this procedure. Seventy-two percent of interns report no formal LP training during medical school. For those who had training, 24% had 1-hour or less of didactic, and 15% had hands-on practice with a simulator. Didactic training during medical school has been associated with higher levels of knowledge, skills, and confidence at the start of internship. Methods The content of the video provides learners with expert modeling and a clear description of the component steps of an infant lumbar puncture. This video focuses on the component psychomotor skills and does not cover the thought process involved in deciding when to perform an ILP. The video can be used by novice providers to introduce them to the procedure and develop their knowledge, skills, and confidence related to the ILP procedure. More experienced providers can use this video as a skills refresher prior to performing the procedure on a real patient. Results Pediatric interns first-attempt clinical ILP success rate is 45% compared to 75% for senior physicians. The Patient Outcomes in Simulation Education Network conducted a training intervention exploring the effect of viewing this video and a simulation-based training intervention on pediatric interns procedural skills performance. Viewing this video was associated with a 60% first attempt success rate for pediatric interns performing infant lumbar punctures. Discussion As of June 2010, over 500 pediatric interns at 25 leading academic medical centers (approximately 20% of pediatric interns in the United States) have viewed this video as part of their intern orientation process. We expect that many infants will be impacted over the course of the careers of the trainees who have participated in the wide-spread dissemination of this training program. This project has changed the standard of care provided to infants requiring a lumbar puncture at participating hospitals.